Determinan Kinerja Sistem Informasi Akuntansi dimoderasi oleh Pendidikan dan Pelatihan - Victor Pattiasina; Muhamad Yamin Noch; Saling Saling; Melyanus Bonsapia; Andarias Patiran (Univiversitas Dr. Djar Wattiheluw, 2021)
This study examines the determinants of accounting information system performance (a study at PT. PLN Company Jayapura district unit). Testing was carried out on a sample of 71 respondents. The sample method used was purposive sampling. Data collection was carried out by direct survey. Hypothesis testing is tested empirically using moderated regression. The results showed that the technical ability of the apparatus had no effect on the performance of the accounting information system at PT. PLN Company Unit Jayapura Regency, user involvement affects the performance of the accounting information system on the performance of the accounting information system at PT. PLN Jayapura Regency Unit, the sophistication of personnel technology has an effect on the performance of the accounting information system. The performance of the accounting information system at PT. PLN Jayapura Regency Unit Company, training moderates the technical ability of the apparatus on the performance of the accounting information system at PT. PLN Company Unit Jayapura Regency, training moderates user involvement in the performance of the accounting information system at PT. PLN Jayapura Regency Unit and the latest education and training moderated the sophistication of personnel technology on the performance of the accounting information system at PT. PLN Jayapura Regency Unit Company.